Intermediate monocytes exhibit higher levels of TLR2, TLR4 and CD64 early after congenital heart surgery - Merbecks, Moritz B.; Ziesenitz, Victoria C.; Klein, Berthold; Rauch, Helmut; Saur, Patrick; Loukanov, Tsvetomir; Gorenflo, Matthias (Cytokine, 2020)
Introduction - Congenital heart surgery with cardiopulmonary bypass (CPB) initiates an immune response which frequently leads to organ dysfunction and a systemic inflammatory response. Complications associated with exacerbated immune responses may severely impact the postoperative recovery. The objective was to describe the characteristics of monocyte subpopulations and neutrophils at the level of pattern recognition receptors (PRR) and the cytokine response after CPB in infants. - Methods - An observational cohort study was conducted between June 2016 and June 2017 of infants < 2 years of age, electively admitted for surgical correction of acyanotic congenital heart defects using CPB. Fourteen blood samples were collected sequentially and processed immediately during and up to 48 h following cardiac surgery for each patient. Flow cytometry analysis comprised monocytic and granulocytic surface expression of CD14, CD16, CD64, TLR2, TLR4 and Dectin-1 (CLEC7A). Monocyte subpopulations were further defined as classical (CD14/CD16−), intermediate (CD14/CD16+) and nonclassical (CD14+/CD16) monocytes. Plasma concentrations of 14 cytokines, including G-CSF, GM-CSF, IL-1β, IL-1RA, IL-4, IL-6, IL-8, IL-10, IL-12p40, IL-12p70, TNF-α, IFN-γ, MIP-1β (CCL4) and TGF-β1, were measured using multiplex immunoassay for seven points in time. - Results - Samples from 21 infants (median age 7.4 months) were analyzed by flow cytometry and from 11 infants, cytokine concentrations were measured. Classical and intermediate monocytes showed first receptor upregulation with an increase in CD64 expression four hours post CPB. CD64-expression on intermediate monocytes almost tripled 48 h post CPB (p < 0.0001). TLR4 was only increased on intermediate monocytes, occurring 12 h post CPB (p = 0.0406) along with elevated TLR2 levels (p = 0.0002). TLR4 expression on intermediate monocytes correlated with vasoactive-inotropic score (rs = 0.642, p = 0.0017), duration of ventilation (rs = 0.485, p = 0.0259), highest serum creatinine (rs = 0.547, p = 0.0102), postsurgical transfusion (total volume per kg bodyweight) (rs = 0.469, p = 0.0321) and lowest mean arterial pressure (rs = -0.530, p = 0.0135). Concentrations of IL-10, MIP-1β, IL-8, G-CSF and IL-6 increased one hour post CPB. Methylprednisolone administration in six patients had no significant influence on the studied surface receptors but led to lower IL-8 and higher IL-10 plasma concentrations. - Conclusions - Congenital heart surgery with CPB induces a systemic inflammatory process including cytokine response and changes in PRR expression. Intermediate monocytes feature specific inflammatory characteristics in the 48 h after pediatric CPB and TLR4 correlates with poorer clinical course, which might provide a potential diagnostic or even therapeutic target.
Gesehen am 25.09.2020